Magnesium-aluminum composite oxide and preparation method thereof

A two-step anhydrous reaction using n-pentanol and n-hexanol with a catalyst efficiently produces high-purity magnesium-aluminum composite oxide, addressing industrial challenges of impurity introduction and reaction complexity.

CN119143497AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310716289.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

Existing methods for preparing high-purity magnesium-aluminum spinel powder face challenges such as high reaction temperatures, alcohol volatilization, introduction of impurities, and complex operation, making them unsuitable for industrial application.

Method used

A two-step anhydrous reaction process using n-pentanol and n-hexanol with a catalyst to produce magnesium-aluminum composite oxide, avoiding impurity introduction and reducing reaction times.

Benefits of technology

The method achieves high-purity magnesium-aluminum composite oxide (>99.99%) with flexible composition control, short reaction times, and reduced costs without subsequent purification, suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004289831470000131
    Figure BDA0004289831470000131
  • Figure BDA0004289831470000141
    Figure BDA0004289831470000141
  • Figure BDA0004289831470000142
    Figure BDA0004289831470000142
Patent Text Reader

Abstract

The invention relates to the field of magnesium-aluminum composite oxide preparation, and discloses a magnesium-aluminum composite oxide and a preparation method thereof. The method comprises the following steps: (1) under an anhydrous condition, carrying out first reaction on an aluminum simple substance and first fatty alcohol to obtain a material containing alkoxy aluminum; (2) under the action of a catalyst, carrying out a second reaction on the material containing alkoxy aluminum obtained in the step (1), a magnesium elementary substance and second fatty alcohol under an anhydrous condition; (3) hydrolyzing the reaction product in the step (2) to obtain magnesium-aluminum bimetal alkoxide, and then optionally drying and roasting to obtain a magnesium-aluminum composite oxide; wherein the first fatty alcohol and the second fatty alcohol respectively and independently comprise n-amyl alcohol and optional n-hexyl alcohol. According to the preparation method of the magnesium-aluminum composite oxide, provided by the invention, the high-purity magnesium-aluminum composite oxide can be obtained without subsequent purification treatment, and meanwhile, the preparation method has the advantages of short initiation time and short reaction time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of magnesium-aluminum composite oxides, and in particular to a magnesium-aluminum composite oxide and a preparation method thereof. Background Art

[0002] High-purity ultrafine magnesium-aluminum spinel powder (magnesium-aluminum composite oxide) refers to artificially synthesized, generally with a purity of more than 99.99%, and a particle size of submicron to nanometer-level tiny solid particles. Magnesium-aluminum spinel powder was previously mainly used in refractory materials, wear-resistant materials, fine ceramics and pigment industries. In recent years, it has gradually expanded to high-tech fields such as optical performance materials, catalysts and their carrier materials. With the development of laser crystal materials and functional materials, higher requirements are placed on the purity, particle size and chemical uniformity of magnesium-aluminum spinel powder. Therefore, it is of great significance to obtain high-purity, ultrafine, and chemically uniform magnesium-aluminum spinel powder for its application.

[0003] At present, there are many studies on the preparation methods of magnesium-aluminum spinel at home and abroad. The main methods used are solid phase method, precipitation method, sol-gel method, aluminum-magnesium bimetallic alkoxide hydrolysis method, hydrothermal synthesis method, combustion synthesis method, solution evaporation method, etc. The advantages of aluminum-magnesium bimetallic alkoxide hydrolysis method are that it uses metal aluminum, metal magnesium and fatty alcohol as raw materials, no impurity ions are introduced during the reaction process, and it can be further purified by vacuum distillation or recrystallization, and the purity of the obtained magnesium-aluminum spinel powder is higher.

[0004] US6514473B2, US6517795B1, US20010001653A1, CN1109576C and CN1171979A disclose a method for preparing high-purity hydrotalcite by reacting alcohol or alcohol mixture with at least one or more divalent metals and at least one or more trivalent metals and hydrolyzing the obtained alkoxide mixture with water, and the corresponding metal oxide can be prepared by calcining. However, in the whole preparation process, the reaction temperature required for fatty alcohol and metal aluminum and metal magnesium is much higher than the boiling point of fatty alcohol, and a special reaction device is required to carry out the reaction. The reaction conditions are harsh, and the alcohol volatilization loss is large. It is necessary to replenish alcohol multiple times to complete the reaction, which is complicated to operate and increases the cost, and is not conducive to industrial application; adding water-soluble organic or inorganic anions during the hydrolysis process introduces new impurities, and the purity of the obtained product is low, and subsequent filtration and purification treatment is required.

[0005] Therefore, there is an urgent need to develop a simple-to-operate process to prepare high-purity magnesia-alumina spinel powder. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a magnesium-aluminum composite oxide and a preparation method thereof. The preparation method of the magnesium-aluminum composite oxide provided by the present invention can obtain a high-purity magnesium-aluminum composite oxide without subsequent purification treatment, and has the advantages of short initiation time and short reaction time.

[0007] In order to achieve the above object, the present invention provides a method for preparing a magnesium-aluminum composite oxide, which comprises the following steps:

[0008] (1) Under anhydrous conditions, a single aluminum substance and a first fatty alcohol are subjected to a first reaction to obtain a material containing an alkoxy aluminum;

[0009] (2) in the presence of a catalyst, subjecting the alkoxy aluminum-containing material obtained in step (1), magnesium element and a second fatty alcohol to a second reaction under anhydrous conditions;

[0010] (3) hydrolyzing the reaction product of step (2) to obtain a magnesium aluminum bimetallic alkoxide, and then optionally drying and calcining to obtain a magnesium aluminum composite oxide;

[0011] Wherein, the first fatty alcohol and the second fatty alcohol each independently include n-pentanol and optionally n-hexanol, and the molar ratio of n-pentanol to n-hexanol is 1:0-10.

[0012] In the art, those skilled in the art believe that the more positive alcohol reaction rate of carbon atoms is faster, but there is violent reaction, difficult to control problem, simultaneously along with the growth of carbon chain its viscosity is larger, is unfavorable for the carrying out of building-up reactions, usually adopts C2-C4 fatty alcohols such as ethanol, isopropanol, propyl carbinol to prepare magnesium-aluminum composite oxide.In addition, in the reaction of magnesium and fatty alcohol, magnesium metal and fatty alcohol reaction are caused to be more difficult, usually adopts C2-C4 fatty alcohol and magnesium metal to react under the condition of catalyst and / or organic solvent as dispersion agent, and the initiation time is longer, also introduces new impurity.The inventor finds in the research process, adopts the positive alcohol comprising n-pentanol and optionally n-hexyl alcohol to prepare magnesium-aluminum composite oxide with specific two-step reaction under anhydrous condition, can obtain highly purified magnesium-aluminum composite oxide without subsequent purification treatment (such as underpressure distillation, recrystallization etc.), can shorten the initiation time when adopting specific alcohol of the present invention to participate in reaction simultaneously, thereby shortens the overall reaction time of reaction system.

[0013] The second aspect of the present invention provides a magnesium-aluminum composite oxide prepared by the preparation method described in the first aspect.

[0014] Through the above technical solution, the beneficial effects of the present invention include:

[0015] The preparation method provided by the present invention can obtain high-purity magnesium-aluminum composite oxide without subsequent purification treatment, and the purity is greater than 99.99%. At the same time, the magnesium-aluminum ratio in the magnesium-aluminum composite oxide can be flexibly adjusted to meet actual needs.

[0016] Preferably, the preparation method provided by the present invention has the advantages of short initiation time, fast reaction rate, mild reaction conditions, and no introduction of impurities other than those carried by metal magnesium and aluminum. In the preparation method provided by the present invention, the amount of catalyst used is small, which can reduce the preparation cost. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0019] In one aspect, the present invention provides a method for preparing a magnesium-aluminum composite oxide, the method comprising the following steps:

[0020] (1) Under anhydrous conditions, a single aluminum substance and a first fatty alcohol are subjected to a first reaction to obtain a material containing an alkoxy aluminum;

[0021] (2) in the presence of a catalyst, subjecting the alkoxy aluminum-containing material obtained in step (1), magnesium element and a second fatty alcohol to a second reaction under anhydrous conditions;

[0022] (3) hydrolyzing the reaction product of step (2) to obtain a magnesium aluminum bimetallic alkoxide, and then optionally drying and calcining to obtain a magnesium aluminum composite oxide;

[0023] Wherein, the first fatty alcohol and the second fatty alcohol each independently include n-pentanol and optionally n-hexanol, and the molar ratio of n-pentanol to n-hexanol is 1:0-10.

[0024] In the preparation method of the present invention, the reactions in step (1) and step (2) must be carried out under anhydrous conditions to avoid the problem that the alkoxyaluminum generated in step (1) and the alkoxymagnesium aluminum generated in step (2) are hydrolyzed to form hydroxides, which prevents the reaction from continuing.

[0025] The present invention has no particular limitation on the method for achieving anhydrous conditions, and the method can be carried out by conventional technical means in the art. For example, the reaction of the present invention can be carried out in a three-necked flask, and the three-necked flask can be washed and dried in the air or placed in an oven before the reaction to ensure that the three-necked flask is clean and anhydrous.

[0026] It should be noted that the anhydrous conditions described in the present invention do not require complete anhydrous conditions, but only mean that no additional water is introduced, but do not exclude a very small amount of water adsorbed in the air in the raw materials and / or catalysts.

[0027] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, using or not using. Specifically, n-hexanol may or may not be added to the first fatty alcohol and the second fatty alcohol of the present invention.

[0028] According to the present invention, preferably, the first fatty alcohol comprises n-pentanol and n-hexanol, and the molar ratio of n-pentanol to n-hexanol is 1:0.1-1;

[0029] The second fatty alcohol is n-pentanol.

[0030] In the present invention, the molar ratio of n-pentanol to n-hexanol is 1:0.1-1, such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, and any value in the range formed by any two of these values. The use of this preferred embodiment is conducive to obtaining high-purity magnesium-aluminum composite oxides and shortening the reaction initiation time. When the molar ratio of n-pentanol to n-hexanol is higher than the above range, the first reaction initiation time will be significantly increased, thereby extending the overall reaction time of the reaction system; when the molar ratio of n-pentanol to n-hexanol is lower than the above range, the purity of the magnesium-aluminum composite oxide will be reduced.

[0031] According to the present invention, preferably, the temperature of the first reaction is 20°C below the boiling point of the first fatty alcohol to the boiling point of the first fatty alcohol, preferably 20°C below the boiling point of the first fatty alcohol to 2°C below the boiling point of the first fatty alcohol. With this preferred embodiment, a relatively high reaction rate can be maintained while avoiding the incomplete reaction caused by the volatilization loss of the first fatty alcohol due to excessively high temperature.

[0032] When the first fatty alcohol includes n-pentanol and n-hexanol, the temperature of the first reaction is based on the boiling point of n-pentanol.

[0033] The initiation time of the present invention refers to the time from the start of heating to the reaction temperature to the observation of continuous large-scale bubble generation (or bubble generation in clusters) of the solution. The preparation method provided by the present invention can significantly shorten the initiation time of the first reaction. According to the present invention, preferably, the initiation time of the first reaction is 0.2-4.5h, preferably 0.2-0.5h.

[0034] The reaction time of the present invention refers to the time from the observation of continuous large-scale bubble generation (or bubble generation in clusters) of the solution to the observation of no obvious bubble generation of the solution. The preparation method provided by the present invention can significantly shorten the reaction time of the first reaction. Preferably, the reaction time of the first reaction is 0.4-4h, preferably 0.5-2h.

[0035] According to the present invention, preferably, the molar ratio of the aluminum element to the first fatty alcohol is 1:3-5, preferably 1:3.1-4.5. This preferred embodiment is conducive to the complete reaction of the aluminum element.

[0036] According to the present invention, preferably, the purity of the aluminum element is not less than 99.9% by mass. This preferred embodiment is conducive to obtaining a high-purity magnesium-aluminum composite oxide.

[0037] The present invention has no particular limitation on the form of the aluminum element, which can be selected conventionally in the art. Preferably, the aluminum element is selected from at least one of aluminum blocks, aluminum beans, aluminum sheets, aluminum wires and aluminum chips.

[0038] The aluminum blocks, aluminum beans, aluminum sheets, aluminum wires, and aluminum chips described in the present invention are well known to those skilled in the art, and will not be described in detail herein.

[0039] According to a specific embodiment of the present invention, the alkoxy aluminum-containing material obtained in step (1) is first cooled to 80-100° C., and then the second reaction is carried out. This preferred embodiment can effectively reduce the volatilization of alcohol.

[0040] According to the present invention, preferably, the temperature of the second reaction is 20°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol, preferably 10°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol. In this preferred embodiment, if the second reaction temperature is lower than the above range, the reaction is difficult to initiate and the reaction rate is slow; if the second reaction temperature is higher than the above range, the fatty alcohol is easily volatilized and lost, resulting in incomplete reaction.

[0041] The definition of the initiation time of the second reaction of the present invention is the same as that of the initiation time of the first reaction.

[0042] The preparation method provided by the present invention can significantly shorten the initiation time of the second reaction. Preferably, the initiation time of the second reaction is 0.25-5h, preferably 0.25-0.5h.

[0043] The definition of reaction time of the second reaction of the present invention is the same as that of the first reaction.

[0044] The preparation method provided by the present invention can significantly shorten the reaction time of the second reaction. Preferably, the reaction time of the second reaction is 0.4-4h, preferably 0.6-3h.

[0045] According to the present invention, preferably, the molar ratio of the magnesium element to the second fatty alcohol is 1: 2-7, preferably 1: 2-4. With this preferred embodiment, the reaction can be completed quickly and fully while avoiding excessive fatty alcohol waste, which can save costs.

[0046] Preferably, the molar ratio of the magnesium element to the aluminum element is 1:0.3-3, preferably 1:0.5-2. By adopting this preferred embodiment, alkoxy magnesium aluminum can be fully dispersed to ensure the smooth progress of the reaction.

[0047] Preferably, the mass ratio of the catalyst to the total reactant of step (2) is 1:100-300, preferably 1:100-200, wherein the total reactant is the alkoxy aluminum-containing material obtained in step (1), magnesium element and the second fatty alcohol. By adopting this preferred method, the amount of catalyst used is greatly reduced while the reaction rate is increased, which can reduce the cost.

[0048] The present invention has a wide range of catalyst types, which can be conventionally selected in the art. Preferably, the catalyst is selected from at least one of iodine, mercuric dichloride and aluminum chloride. In order to further increase the reaction rate and not introduce other impurities, the catalyst is preferably iodine.

[0049] According to the present invention, preferably, the purity of the magnesium element is not less than 99.9% by mass. This preferred embodiment is conducive to obtaining a high-purity magnesium-aluminum composite oxide.

[0050] The present invention has no particular limitation on the form of the magnesium element, which can be a conventional choice in the art. Preferably, the magnesium element is selected from at least one of magnesium blocks, magnesium sheets, magnesium wires, magnesium chips, magnesium particles, magnesium strips and magnesium powders.

[0051] The magnesium blocks, magnesium sheets, magnesium wires, magnesium chips, magnesium particles, magnesium bars and magnesium powder described in the present invention are well known to those skilled in the art and will not be described in detail herein.

[0052] According to the present invention, preferably, the first reaction and / or the second reaction is carried out under condensation reflux conditions.

[0053] Preferably, before adding the reaction materials into the reactors of the first reaction and the second reaction, the reactors are purged with inert gas to replace the air therein. With this preferred embodiment, the surface oxidation of elemental aluminum and elemental magnesium can be prevented while drying the interior of the reactor.

[0054] The present invention has a wide range of selection for the inert gas, and any gas that does not affect the reaction can be used. The inert gas of the present invention is preferably nitrogen.

[0055] In the hydrolysis process of the present invention, no additives such as hydroxide anions, organic anions (especially alkoxide ions, alkoxy ether sulfates, aryl ether sulfates, glycol ether sulfates), inorganic anions (carbonate, bicarbonate, chloride, nitrate, sulfate, polyoxymetallic anions) are added, so that the purpose of full hydrolysis can be achieved without introducing new impurities and without subsequent impurity removal treatment. In addition, in the hydrolysis process of step (3) of the present invention, the hydrolysis temperature and the amount of water added are controlled within the following ranges, which is conducive to the full hydrolysis of alkoxy magnesium aluminum, while reducing the amount of water used and saving costs.

[0056] According to the present invention, preferably, the hydrolysis temperature in step (3) is 60-100°C, preferably 85-95°C.

[0057] The present invention has no particular limitation on the hydrolysis time, as long as the slurry after hydrolysis has good fluidity and does not adhere to the wall.

[0058] According to the present invention, preferably, the mass ratio of the reaction product of step (2) to water is 1:1-5, preferably 1:1.1-3.5.

[0059] According to the present invention, preferably, the method further comprises: separating the material obtained by the hydrolysis in step (3), and then optionally drying and roasting it to obtain the magnesium-aluminum composite oxide.

[0060] The present invention has no particular limitation on the separation method, and the separation can be carried out using conventional techniques in the art.

[0061] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, adopting or not adopting. Specifically, step (3) of the present invention may be dried or not dried.

[0062] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art.

[0063] According to the present invention, preferably, the calcination conditions in step (3) include: a temperature of 550-850°C and a time of 4-8 hours. The calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a static atmosphere.

[0064] According to a particularly preferred embodiment of the present invention, a method for preparing a magnesium-aluminum composite oxide comprises the following steps:

[0065] (1) Under anhydrous conditions, a single aluminum substance and a first fatty alcohol are subjected to a first reaction to obtain a material containing an alkoxy aluminum;

[0066] (2) in the presence of a catalyst, subjecting the alkoxy aluminum-containing material obtained in step (1), magnesium element and a second fatty alcohol to a second reaction under anhydrous conditions;

[0067] (3) hydrolyzing the reaction product of step (2) to obtain a magnesium aluminum bimetallic alkoxide, and then optionally drying and calcining to obtain a magnesium aluminum composite oxide;

[0068] Wherein, the first fatty alcohol comprises n-pentanol and n-hexanol, the molar ratio of n-pentanol to n-hexanol is 1:0.1-1, and the second fatty alcohol is n-pentanol;

[0069] The temperature of the second reaction is 20°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol, preferably 10°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol;

[0070] The initiation time of the second reaction is 0.25-0.5h;

[0071] The reaction time of the second reaction is 0.6-3h;

[0072] The molar ratio of the magnesium element to the second fatty alcohol is 1:2-4;

[0073] The molar ratio of the magnesium element to the aluminum element is 1:0.5-2.

[0074] The specific preparation method of the present invention can obtain high-purity magnesium-aluminum composite oxide without subsequent purification treatment, and the purity is higher than 99.99%. At the same time, the preparation method provided by the present invention has the advantages of mild reaction conditions, short initiation time, fast reaction rate, and no introduction of impurities other than impurities carried by metal magnesium and aluminum. Preferably, the preparation method provided by the present invention uses less catalyst, which can reduce the preparation cost.

[0075] The second aspect of the present invention provides a magnesium-aluminum composite oxide prepared by the preparation method described in the first aspect.

[0076] The high-purity magnesium-aluminum composite oxide prepared by the method of the present invention is widely used, for example, in catalyst preparation. According to the present invention, preferably, the purity of the magnesium-aluminum composite oxide is greater than 99.99%.

[0077] The present invention will be described in detail below through examples.

[0078] In the following examples, the magnesium-aluminum ratio and product purity of the magnesium-aluminum composite oxide were measured by inductively coupled plasma (ICP);

[0079] In the following examples, all reagents used were commercially available and of analytical grade.

[0080] Example 1

[0081] (1) Wash the three-necked flask in advance and put it into an oven to dry to ensure that the three-necked flask is clean and free of water. Purge the three-necked flask with nitrogen before the test. Add 6.76g of aluminum wire with a purity of 99.996% by mass into the three-necked flask with a heating and condensing system, take 86.85g of n-pentanol, add it into the three-necked flask to immerse the aluminum wire. Gradually heat it to 135°C (the boiling point of n-pentanol is 137.8°C), and keep condensing and reflux until the solution has no obvious bubbles and there is no aluminum wire in the solution. Then cool it to 100°C. The initiation time and reaction time of the reaction are shown in Table 1.

[0082] (2) Add 3.01 g of magnesium chips with a purity of 99.9% by mass, 0.67 g of iodine with a purity of 99.8% by mass, and 35.42 g of n-pentanol to 92.86 g of the n-pentyl aluminum n-pentanol solution obtained by the above reaction; gradually heat to 135° C. and keep condensing and refluxing until no obvious bubbles are generated in the solution and no magnesium chips remain in the solution, and the reaction is completed. The initiation time and reaction time of the reaction are shown in Table 1.

[0083] (3) 131.04g of the n-pentyloxy magnesium aluminum n-pentanol solution obtained in step (2) was maintained at 90°C and transferred to a 1000mL beaker, and 90°C deionized water was added for hydrolysis until the solution was layered and the lower slurry had good fluidity and the slurry did not adhere to the wall, and 350g of deionized water was used. A magnesium aluminum hydroxide slurry phase and a n-pentanol phase were obtained, and the upper n-pentanol phase was separated, and the magnesium aluminum hydroxide slurry was placed in a blast constant temperature drying oven, dried at 120°C for 12 hours, and then placed in a muffle furnace and calcined at 600°C for 6h to obtain a magnesium aluminum composite oxide. The magnesium aluminum ratio and product purity obtained by inductively coupled plasma (ICP) analysis are shown in Table 2.

[0084] Example 2

[0085] (1) Wash the three-necked flask in advance and put it into an oven to dry to ensure that the three-necked flask is clean and free of water. Purge the three-necked flask with nitrogen before the test. Add 2.69g of the aluminum wire used in Example 1 into the three-necked flask with a heating and condensing system, take 28.30g of n-pentanol and 10.22g of n-hexanol and add them into the three-necked flask to immerse the aluminum wire. Gradually raise the temperature to 135°C and keep condensing and reflux until no obvious bubbles are generated in the solution and there is no aluminum wire in the solution. Then cool it down to 100°C. The initiation time and reaction time of the reaction are shown in Table 1.

[0086] (2) 2.40 g of magnesium chips used in Example 1 were added to 39.06 g of the solution obtained by the above reaction, 0.50 g of iodine with a purity of 99.8% by mass, and 27.24 g of n-pentanol were added to a three-necked flask; the temperature was gradually raised to 130 ° C, and condensation reflux was maintained until the solution had no obvious bubbles and no magnesium chips remained in the solution, and the reaction was terminated. The initiation time and reaction time of the reaction are shown in Table 1.

[0087] (3) 68.5 g of the n-pentanol solution of alkoxy magnesium aluminum obtained in step (2) was maintained at 90° C. and transferred to a 1000 mL beaker, and 90° C. deionized water was added for hydrolysis until the solution was separated and the lower slurry had good fluidity and did not adhere to the wall. 210 g of deionized water was used. A magnesium aluminum hydroxide slurry phase and a n-pentanol phase were obtained, and the upper n-pentanol phase was separated. The magnesium aluminum hydroxide slurry was placed in a blast constant temperature drying oven, dried at 120° C. for 12 hours, and then placed in a muffle furnace for calcination at 600° C. for 6 hours to obtain a magnesium aluminum composite oxide. The magnesium aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis as shown in Table 2.

[0088] Example 3

[0089] The method of Example 1 was followed, except that the n-pentanol in step (1) was replaced with 44.08 g n-pentanol and 49.56 g n-hexanol to obtain a magnesium-aluminum composite oxide. The magnesium-aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis and are shown in Table 2.

[0090] Example 4

[0091] The method of Example 1 was followed, except that the temperature of the first reaction and the second reaction was 137° C. After the first reaction, there was still unreacted aluminum chips, and n-pentanol solution needed to be supplemented until the reaction was complete. After the second reaction, there was still unreacted magnesium chips, and n-pentanol solution needed to be supplemented until the reaction was complete. The operation was cumbersome and increased the cost, which was not conducive to industrial application.

[0092] The magnesium-aluminum composite oxide was obtained, and its magnesium-aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis (see Table 2).

[0093] Comparative Example 1

[0094] High-purity alkoxy magnesium aluminum was prepared according to the method of Example 1, except that 6.78 g of the aluminum wire used in Example 1, 3.01 g of the magnesium chips used in Example 1, and 0.60 g of the iodine element used in Example 1 were added into a three-necked flask at the same time, and reacted together with 106.27 g of n-pentanol at 135° C. After the reaction for 36 hours, a large amount of aluminum wire and magnesium chips (about 9.02 g) still remained, indicating that the reaction was not thorough.

[0095] The magnesium-aluminum composite oxide was obtained, and its magnesium-aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis (see Table 2).

[0096] Comparative Example 2

[0097] In a three-necked flask with a heating and condensing system, 3.42 g of magnesium chips used in Example 1 were first added, and then 33.50 g of n-pentanol was added to immerse the magnesium chips. The temperature was gradually raised to 135° C., and condensation and reflux were maintained. The generated alkoxy magnesium adhered to the bottom of the three-necked flask, resulting in the inability to continue the reaction and the magnesium-aluminum composite oxide could not be obtained.

[0098] Comparative Example 3

[0099] The method of Example 1 was followed, except that the n-pentanol in the reactions of step (1) and step (2) was replaced by an equal molar amount of n-butanol, respectively, and the reaction temperature was 115°C (the boiling point of n-butanol is 117.25°C) to obtain a magnesium-aluminum composite oxide. The magnesium-aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis and are shown in Table 2.

[0100] Comparative Example 4

[0101] The method of Example 2 was followed, except that n-pentanol and n-hexanol in step (1) were replaced by 43.02 g of n-hexanol, and the reaction temperature was 150° C. to obtain a magnesium-aluminum composite oxide. The magnesium-aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis and are shown in Table 2.

[0102] Comparative Example 5

[0103] (1) The three-necked flask was placed in an oven for drying in advance to ensure that the three-necked flask was clean and free of water. The three-necked flask was purged with nitrogen before the test. 6.77 g of the aluminum wire used in Example 1 was added to the three-necked flask with a heating and condensing system, and 106.33 g of n-hexanol was added to the three-necked flask to immerse the metal aluminum. The temperature was gradually raised to 150° C. (the boiling point of n-hexanol is 157° C.) to allow the n-hexanol and the high-purity aluminum wire to react, and the condensation reflux was maintained until no obvious bubbles were generated in the solution and no high-purity aluminum wire was present in the solution, and then the temperature was lowered to 100° C. The initiation time and reaction time of the reaction are shown in Table 1.

[0104] (2) 6.01 g of the magnesium chips used in Example 1 were added to the n-hexyl aluminum n-hexanol solution obtained by the above reaction in step (1), 1.22 g of iodine with a purity of 99.8% by mass, and 101 g of n-hexanol were added to a three-necked flask; the temperature was gradually raised to 150° C. to allow the n-hexanol and high-purity magnesium chips to react, and the condensation reflux was maintained until no obvious bubbles were generated in the solution and no magnesium chips remained in the solution, and the reaction was terminated. The initiation time and reaction time of the reaction are shown in Table 1.

[0105] (3) 218.86g of n-hexyl magnesium aluminum n-hexanol solution was maintained at 90°C and transferred to a 1000mL beaker, and 90°C deionized water was added for hydrolysis until the solution was separated and the lower slurry had good fluidity. 315g of deionized water was used. Magnesium aluminum hydroxide slurry phase and n-hexanol phase were generated, and the upper n-hexanol phase was separated. The magnesium aluminum hydroxide slurry was placed in a blast constant temperature drying oven and dried at 120°C for 12 hours to obtain a high-purity magnesium aluminum hydroxide composite. The above-mentioned magnesium aluminum hydroxide composite was placed in a muffle furnace and calcined at 600°C for 6h to obtain a high-purity magnesium aluminum composite oxide. The magnesium aluminum ratio and product purity were obtained by inductively coupled plasma (ICP) analysis as shown in Table 2.

[0106] Table 1

[0107]

[0108]

[0109] Table 2

[0110]

[0111] It can be seen from the results in Table 2 that the specific preparation method of the present invention can obtain high-purity magnesium-aluminum composite oxides with a purity greater than 99.99% without subsequent purification treatment. At the same time, the magnesium-aluminum ratio in the magnesium-aluminum composite oxide can be flexibly adjusted to meet actual needs.

[0112] It can be seen from the results in Table 1 that the preparation method provided by the present invention has the advantages of short initiation time and fast reaction rate.

[0113] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a magnesium-aluminum composite oxide, characterized in that: The method comprises the following steps: (1) Under anhydrous conditions, a single aluminum substance and a first fatty alcohol are subjected to a first reaction to obtain a material containing an alkoxy aluminum; (2) in the presence of a catalyst, subjecting the alkoxy aluminum-containing material obtained in step (1), magnesium element, and a second fatty alcohol to a second reaction under anhydrous conditions; (3) hydrolyzing the reaction product of step (2) to obtain a magnesium aluminum bimetallic alkoxide, and then optionally drying and calcining to obtain a magnesium aluminum composite oxide; Wherein, the first fatty alcohol and the second fatty alcohol each independently include n-pentanol and optionally n-hexanol, and the molar ratio of n-pentanol to n-hexanol is 1:0-10.

2. The method according to claim 1, wherein: The first fatty alcohol includes n-pentanol and n-hexanol, and the molar ratio of n-pentanol to n-hexanol is 1:0.1-1; The second fatty alcohol is n-pentanol.

3. The method according to claim 1, wherein: The temperature of the first reaction is 20°C below the boiling point of the first fatty alcohol to the boiling point of the first fatty alcohol, preferably 20°C below the boiling point of the first fatty alcohol to 2°C below the boiling point of the first fatty alcohol; Preferably, the initiation time of the first reaction is 0.2-4.5h, preferably 0.2-0.5h; Preferably, the reaction time of the first reaction is 0.4-4h, preferably 0.5-2h; Preferably, the molar ratio of the aluminum element to the first fatty alcohol is 1:3-5, preferably 1:3.1-4.5; Preferably, the purity of the aluminum element is not less than 99.9 mass %.

4. The method according to any one of claims 1 to 3, wherein: The temperature of the second reaction is 20°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol, preferably 10°C below the boiling point of the second fatty alcohol to 2°C below the boiling point of the second fatty alcohol; Preferably, the initiation time of the second reaction is 0.25-5h, preferably 0.25-0.5h; Preferably, the reaction time of the second reaction is 0.4-4h, preferably 0.6-3h.

5. The method according to any one of claims 1 to 4, wherein: The molar ratio of the magnesium element to the second fatty alcohol is 1:2-7, preferably 1:2-4; Preferably, the molar ratio of the magnesium element to the aluminum element is 1:0.3-3, preferably 1:0.5-2; Preferably, the mass ratio of the catalyst to the total reactants of step (2) is 1:100-300, preferably 1:100-200, wherein the total reactants are the alkoxy aluminum-containing material obtained in step (1), magnesium element and the second fatty alcohol.

6. The method according to any one of claims 1 to 5, wherein: The catalyst is selected from at least one of iodine, mercuric dichloride and aluminum chloride, preferably iodine; Preferably, the purity of the magnesium element is not less than 99.9 mass %.

7. The method according to any one of claims 1 to 6, wherein: The first reaction and / or the second reaction is carried out under condensation reflux conditions.

8. The method according to any one of claims 1 to 7, wherein: The hydrolysis temperature in step (3) is 60-100°C, preferably 85-95°C; Preferably, the mass ratio of the reaction product of step (2) to water is 1:1-5, preferably 1:1.1-3.

5.

9. The method according to any one of claims 1 to 8, wherein: The calcination conditions in step (3) include: temperature of 550-850° C. and time of 4-8 hours.

10. The magnesium-aluminum composite oxide prepared by the preparation method according to any one of claims 1 to 9; Preferably, the purity of the magnesium-aluminum composite oxide is greater than 99.99%.

Citation Information

Patent Citations

  • Preparation method of magnesium aluminate spinel mesoporous carrier material

    CN115043418A

  • Activated preparation of metal alkoxides

    US4670573A